Evaluation of the Effect of Improvers: Psyllium and Xanthan Gum in Bread Loaf with Partial Replacement of Quinoa Flour - Laidy Quinte; Ingrid Valderrama; Ivan Best (Foods)
Wheat flour (WF) was replaced with quinoa flour (QF) at a 20% level in combination with improvers such as psyllium (PSY) and xanthan gum (XG). The flour quality, dough rheology, baking quality, and sensory evaluation of the bread loaves were analyzed, considering the addition of improvers as follows: PSY 0.5%, XG 0.5%, and PSY 0.25% + XG 0.25%. The best treatment to produce bread loaves was with the application of PSY 0.25% + XG 0.25%, where it had an optimal acceptability and no significant texture difference (p ≥ 0.05) compared with the control, with manageable dough, ideal viscosity, intermediate width/height ratio, and moderate baking stability, reflected in reduced baking losses. The techno-functional and nutritional properties of QF offer a viable alternative to WF.